The Challenges of Changing Scenario in Indian Education System - Payal Arora (AG Volumes, 2022)
The global community has come to the conclusion that a nation’s educational system has a direct influence on its level of economic prosperity. A nation’s strength increases with its level of education. A highly educated population is a hallmark of a developed country. In terms of student enrollment, India’s higher education system is third biggest worldwide, behind only that of the United States and China. While other emerging nations like China and Vietnam are making rapid strides in education since independence, India is making only slow, hesitant gains. While India’s higher education system has faced many obstacles, the country also has several openings through which to improve its offerings. Improved openness and responsibility, the changing role of universities in the 21st century, and the latest findings from the scientific study of learning are all crucial. India’s economic growth depends on the efforts of educated, competent citizens. Since India exports its highly educated population, it will have no trouble making the transition from a developing to a developed nation. The purpose of this research is to draw attention to the problems plaguing India’s university system and to outline its potential solutions.